Macro and microeconomic analysis of the impact of the COVID-19 pandemic in Chile and the projections of the central bank's - Barra Novoa, Rodrigo (International research journal of management, IT and social sciences, 2021)
This article offers a first approximation of the impacts of the COVID-19 pandemic on the Chilean macro and microeconomic environment, using representative data from the latest formal surveys in the country. Here, the number of active firms plummeted in part due to the social crisis that began on October 18, 2019, and losses were felt in most industries due to the pandemic crisis that continues to generate job losses and low business profitability. These first results have implications for central bank policies and can predict medium and medium-term projections, especially for the country's economic and social growth.